South Africa's response to the Covid-19 pandemic: The crisis in the context of the history of South African capitalism - Ben Scully (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
This paper is part of a comparative project on the Varieties of Covid-19 Reactions and Changing Modes of Globalization in the Global South. The project employs a comparative analysis of two industries-automobiles and clothing/textiles-across four countries in order to analyze the impacts of the Covid-19 pandemic on the structure of globalization. However, one of the premises of the project is that any such assessment must be historically contextualized. In order to understand how the world economy and each country was impacted, it is necessary to understand the context into which the pandemic arrived. This paper provides this background context for the country of South Africa. The South African case illustrates the importance of our historically contextual approach, as we argue that the main effect of the pandemic was that it accelerated economic and political trends which were ongoing before 2020. To summarize these trends, the pandemic crisis has opened up ideological and political space for South Africa to depart from neoliberal orthodoxy in ways that seemed unlikely before the pandemic. However it has simultaneously induced economic and fiscal constraints which have reinforced and even exacerbated the global imbalances of power which define neoliberal globalization.
Keywords: I18; L50; O55; P16; 330; Covid-19; South Africa; Industrial Policy; Social Policy; Neoliberalism